2003
DOI: 10.1038/sj.bjp.0705502
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of dronedarone on both components of the cardiac delayed rectifier K+ current, HERG and KvLQT1/minK potassium channels

Abstract: 1 Dronedarone is a noniodinated benzofuran derivative that has been synthesized to overcome the limiting iodine-associated adverse effects of the potent antiarrhythmic drug amiodarone. In this study, the acute electrophysiological effects of dronedarone on repolarizing potassium channels were investigated to determine the class III antiarrhythmic action of this compound. HERG and KvLQT1/ minK potassium channels conduct the delayed rectifier potassium current I K in human heart, being a primary target for class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…Inhibition of I Kr is a common side effect of a large number of noncardiac drugs and has been associated with the development of malignant ventricular arrhythmias (Torsade-de-Pointes). However, inhibition of the same current has also been linked to antiarrhythmic properties and several well-known antiarrhythmics, like amiodarone, dronedarone, and ajmaline inhibit I Kr [78][79][80]. Only recently, we screened a broad spectrum of flavonoids and showed that among others, the citrus flavonoids hesperetin and naringenin potently block hERG potassium channels, which form the molecular basis of I Kr in humans [81][82][83].…”
Section: Inhibition Of Cardiac Potassium Currentsmentioning
confidence: 99%
“…Inhibition of I Kr is a common side effect of a large number of noncardiac drugs and has been associated with the development of malignant ventricular arrhythmias (Torsade-de-Pointes). However, inhibition of the same current has also been linked to antiarrhythmic properties and several well-known antiarrhythmics, like amiodarone, dronedarone, and ajmaline inhibit I Kr [78][79][80]. Only recently, we screened a broad spectrum of flavonoids and showed that among others, the citrus flavonoids hesperetin and naringenin potently block hERG potassium channels, which form the molecular basis of I Kr in humans [81][82][83].…”
Section: Inhibition Of Cardiac Potassium Currentsmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33] In patch clamp experiments using human atrial myocytes, 3 mol/L of dronedarone produced potent blockade of peak sodium current, an effect 10-fold greater than that of an equal concentration of amiodarone. 23 In guinea pig ventricular myocytes, dronedarone inhibited the rapidly activating delayed-rectifier potassium current, the slowly activating delayed-rectifier potassium current, the inward rectifier potassium current, and L-type calcium current.…”
Section: Electrophysiological Properties Of Dronedarone In Vitro Expementioning
confidence: 99%
“…In dogs with healed myocardial infarction, dro ne da rone did not reduce measures of myocardial contractile function, 12 nor did it reduce the left ventricular ejection fraction in patients with compensated heart failure and an ejection fraction of less than 30%. 13 However, dro ne da rone affects the inward sodium channels in the cardiac-cell membrane, 14,15 and other drugs with this property do reduce left ventricular contractility. 16 In ANDROMEDA (Antiarrhythmic Trial with Dro ne da rone in Moderate to Severe CHF Evaluating Morbidity Decrease, NCT00543699) involving 627 patients with heart failure and severe left ventricular systolic dysfunction, 17 dro ne da rone increased mortality, an effect that was largely attributed to heart failure and that suggested a negative inotropic effect of dro ne da rone.…”
Section: Discussionmentioning
confidence: 99%